Assessment of cardiac autonomic functions and anxiety sensitivity scale in different phases of menstrual cycle in young females - Khanam, Gulnaaz; Singh, Shraddha; Ubaidullah, Mohammed; Verma, Dileep Kumar (International Journal of Research in Medical Sciences, 2026)
Background: The menstrual cycle, a reproductive rhythm marked by bleeding and ovulation, is a dynamic biological process where hormones quietly reshape multiple systems in the body with their fluctuations. Cardiovascular control, emotional reactivity and stress responsiveness are the changes which become relevant in young women. Objectives were to measure heart rate variability (HRV) and anxiety sensitivity in different phases of menstrual cycle and establish their correlation. Methods: This study was a comparative (observational) consisting of 48 healthy females’ participants aged 18-32 years. Cardiac autonomic function was assessed using HRV analysis on day 2, day 10, and day 21 of the menstrual cycle While anxiety sensitivity was assessed using the anxiety sensitivity index-3 (ASI-3), an 18-item scale, containing items specifying different concerns someone could have regarding their anxiety. The total ASI-3 score was analysed and compared across the menstrual phases to observe variations in anxiety sensitivity. Correlation between HRV parameters and anxiety sensitivity scores was also assessed to study the relationship between cardiac autonomic function and anxiety sensitive. Results: Both time-domain and frequency-domain HRV parameters, remained largely stable across follicular, and luteal phases. No statistically significant phase-wise differences were observed. In contrast, anxiety sensitivity exhibited a statistically significant variation across menstrual cycle phases, reflecting meaningful phase-related psychological fluctuation. However, this variation in anxiety sensitivity was not accompanied by corresponding changes in resting HRV parameters, and no consistent association was identified between anxiety sensitivity categories and cardiac autonomic indices across phases.